Nitrogen and sulfur co-doped graphene supported PdW alloys as highly active electrocatalysts for oxygen reduction reaction. (15th March 2018) - Sun, Xiang; Li, Wanhui; Mi, Hongwei; Li, Yongliang; Zhang, Peixin; Ren, Xiangzhong
Abstract: Nitrogen and sulfur co-doped graphene (NSG) is prepared by a facile microwave irradiation method and palladium-tungsten (PdW) alloy nanoparticles are supported on the NSG substrate. Several techniques, including X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, cyclic voltammetry and scanning electrochemical microscopy etc. are used to characterize the physical and electrochemical properties of the as-prepared samples. It is found that the PdW alloy nanoparticles are uniformly dispersed on the surface of NSG and the electrochemical performance of PdW/NSG is much better than those of Pd/NSG and Pd/G. The reason for the improved electrochemistry performance of PdW/NSG is considered to be the strong interactions and synergetic effects between PdW nanoparticles and NSG. Highlights: N, S co-doped graphene (NSG) is prepared by microwave irradiation method. PdW alloyed nanoparticles are well dispersed on the NSG. PdW/NSG shows better catalytic activity and stability towards ORR. SECM is used to characterize the electrochemical properties.